PROBLEMS OF EVALUATING BLOOD PRESSURE MEASUREMENT IN MODERN CLINICAL TRIALS (THE CASE OF SPRINT STUDY RESULTS) - V. M. Gorbunov (Столичная издательская компания, 2018)
The article presents a critical analysis of the results of a large clinical trial SPRINT. The focus is on the issues related to the blood pressure (BP) measurement in this trial.The aim of SPRINT trial was to prove the benefit of reducing systolic BP (SBP) below 120 mm Hg in high-risk hypertensive patients. A total, 9,631 highrisk participants without history of diabetes mellitus or stroke were randomly allocated to a standard treatment group (target SBP<140 mm Hg) or an intensive treatment group (target SBP<120 mm Hg). Significantly lower rates of all-cause mortality (by 27%) and cardiovascular events (by 25%) were observed in the intensive treatment group, compared to the standard treatment one. Therefore, the intervention was stopped early, after a mean follow-up of 3.3 years (instead of 5 years, as specified in the study protocol).However, the SPRINT study used an unusual method of clinical BP measurement, the so-called automatic office BP (AOBP) measurement. An important feature of AOBP is that it provides significantly lower BP values, compared to the conventional clinic BP measurement. This article reviews the publications which aimed to provide an independent evaluation of the SPRINT results. It appears that if traditional clinic BP measurement was used in SPRINT, the mean SBP level in the control group could be approximately 150 mm Hg, which is substantially higher than the generally accepted threshold of 140 mm Hg. This could explain a higher prevalence of cardiovascular events in the control group. The estimated SBP level in the intensive treatment group (132-136 mm Hg) is not very different from the standard threshold.Therefore, the SBP target in the treatment of hypertension remains unchanged at <140 mm Hg. AOBP is a specific subtype of the clinic BP measurement. The currently proposed AOBP threshold (135/85 mm Hg) warrants further investigation.